Effect of Decompressive Craniectomy with Stepwise Decompression of the Intracranial Compartment on Postoperative Neurologic Function, Hemodynamics, and Glasgow Outcome Scale Score of Patients with Severe Traumatic Brain Injury - Wu, Huayong; Jiang, Bingjie; Yan, Xinjiang; Zhan, Chengpeng; Dai, Weimin; Yu, Guofeng (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background We assess the effects of standard decompressive craniectomy with stepwise decompression of the intracranial compartment on the postoperative neurologic function, hemodynamics, and Glasgow Outcome Scale (GOS) score of patients with severe traumatic brain injury (sTBI).Methods One hundred sTBI patients admitted from July 2017 to February 2019 were enrolled and randomly divided into step and standard groups (n = 50) using a random number table. The standard group received traditional standard decompression during surgery, while the step group underwent multistep decompression during surgery. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were measured immediately after surgery (T0), 3 hours after surgery (T1), 6 hours after surgery (T2), and 12 hours after surgery (T3). The postoperative Glasgow Coma Scale (GCS) score, neurologic function deficit score, and GOS score were evaluated.Results After treatment, the excellent/good rate of neurologic function improvement and GCS and GOS scores of the step group significantly exceeded those of the standard group (p < 0.05). Compared with the standard group, the HR, SBP, DBP, and MAP decreased significantly in the step group at T1, T2, and T3 (p < 0.05).Conclusion Standard decompressive craniectomy under multistep decompression can markedly improve the neurologic function, hemodynamics, and prognosis of patients.
Keywords: multistep decompression; standard decompressive craniectomy; severe traumatic brain injury; neurologic function; hemodynamics; Glasgow Outcome Scale